The Role of Human Resources in the Implementation of Cooperative Management to Improve Cooperative Performance Al Washliyah Muslim University - Rahmat, Muhammad; Pasaribu, Fajar; Iskandar Batubara, Dedi; Siagian, Hendra Sakti Putra; Roy Purba, Roberto (AIBPM Publisher, 2025)
Human resources have a good role for every organization individually or in groups, human resources are the main driver in the smooth running of business activities, even the development of the company is determined by human resources. Good management is needed in a company as well as in a cooperative so that human resources can be used properly. Management ensures that the resources owned by the cooperative are used effectively and efficiently. Good cooperative management will create a cooperative that determines the success of achieving the vision, mission and goals of the cooperative. The implementation of good cooperatives is important to achieve the expected goals. Cooperative activities cannot be separated from the role of members in it, for this reason the welfare of members is one of the goals that must be achieved. This research is a narrative inquiry with a qualitative approach. This research is to see the implementation of employees in implementing the concepts, definitions, and empirical indicators of Cooperative Management. The results of this study show that employees are able to carry out their duties, principals and functions in accordance with the Standard Operating Procedures in decision-making, and employees have a good role in managing cooperatives.